Silicon-containing negative pole piece, preparation method thereof and lithium ion battery
By doping silicon-containing active materials in the porous current collector and installing a protective layer, the problem of poor cell circulation performance caused by volume expansion of the silicon-based negative electrode active material is solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202411569594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the negative electrode current collector cannot effectively suppress the volume expansion of the silicon-based negative electrode active material, resulting in poor circulation performance of lithium-ion batteries.
By doping silicon-containing active material in the porous current collector and laying a protective layer on the surface of the porous current collector, the porosity of the porous current collector and the effective radius of the pores are optimized to effectively bind the volume expansion of the silicon particles.
The cycle stability and energy density of lithium-ion batteries are improved, the contact between silicon-containing active materials and electrolytes is reduced, the occurrence of side reactions is reduced, and the circulation performance of the battery is improved.
Smart Images

Figure BDA0005120098430000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-containing negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] As the requirements for battery life of lithium-ion batteries continue to increase, the use of high-gram capacity active materials to increase energy density is an important direction for the development of lithium-ion batteries. Currently, among negative electrode materials, the gram capacity of graphite materials has approached its theoretical gram capacity of 372mAh / g, while the theoretical gram capacity of silicon is 4200mAh / g, which is ten times the capacity of graphite materials. It is expected to become the negative electrode material for the next generation of lithium-ion batteries. However, compared with graphite materials, the volume expansion of silicon negative electrodes is larger during the charging and discharging process, which makes it easy for the active material layer to peel off from the current collector, resulting in a significant attenuation of the cycle performance of lithium-ion batteries. This is the main reason limiting its widespread application.
[0003] The Chinese patent application with the patent application publication number CN117410435A provides a method for preparing a negative electrode sheet and a secondary battery, by embedding active materials, conductive agents and binders in the pores of a porous current collector, and designing the pores of the porous current collector to limit the expansion and contraction of active particles. In addition, the slurry is applied to the current collector by a coating method, but the negative electrode active slurry only partially penetrates into the pores of the porous current collector, and the other part still floats on the surface of the current collector. Part of the material layer in the surface layer is not bound by the three-dimensional current collector, resulting in an unclear confinement effect, so that expansion and powdering peeling will still occur, which will affect the cycle performance of the battery cell.
[0004] The Chinese patent application with the patent application publication number CN117577854A provides a silicon-based negative electrode for an all-solid-state battery and a preparation method thereof, and an all-solid-state battery. The patent adopts a metal current collector with a three-dimensional porous structure as a skeleton, and the porous structure has high rigidity. The silicon-based negative electrode active material is filled in the porous structure to provide the required space for the volume change of the silicon-based negative electrode active material during the charge and discharge process, thereby avoiding the pulverization and cracking of the particles due to the volume change of the silicon particles, thereby improving the cycle life of the battery cell. In addition, the current collector is immersed in the negative electrode slurry containing the silicon-based negative electrode active material by immersion, and after drying and molding, a silicon-based negative electrode is obtained. However, this design is only applicable to all-solid-state battery systems. In the application of liquid batteries, the active layer of the silicon material will still be exposed to the electrolyte environment, resulting in continuous side reactions, thereby affecting the cycle performance of the battery.
[0005] Therefore, the current contact between the current collector and the silicon-containing active layer is only partial, and an effective expansion inhibition effect has not yet been achieved. In addition, due to differences in the applicable battery systems, there is still the problem of large-scale contact between silicon and electrolyte in the liquid system, leading to side reactions. Summary of the invention
[0006] The main purpose of the present invention is to provide a silicon-containing negative electrode plate and a preparation method thereof, and a lithium-ion battery, so as to solve the problem in the prior art that the negative electrode current collector cannot effectively inhibit the volume expansion of the silicon-based negative electrode active material, resulting in poor battery cycle performance.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a silicon-containing negative electrode plate, which comprises a porous current collector and a protective layer stacked on the surface of the porous current collector; wherein the pores of the porous current collector are filled with silicon-containing active materials, the porosity of the porous current collector is 20-50%, and the effective radius of the pores in the porous current collector is 0.05-0.2 mm.
[0008] Furthermore, the mass content of the silicon-containing active material in the porous current collector is 37-55%.
[0009] Furthermore, the surface density of the protective layer accounts for 20-50% of the total surface density of the silicon-containing negative electrode plate; and / or the surface density ratio of the protective layer to the porous current collector is 1:4-1:1.
[0010] Furthermore, the protective layer is selected from any one or more of a secondary particle carbonized artificial graphite layer, a secondary particle uncoated artificial graphite layer and a single particle graphite mixed with a secondary particle graphite layer, and / or the OI value of the protective layer is 2.5 to 3.8.
[0011] According to another aspect of the present invention, a method for preparing the above-mentioned silicon-containing negative electrode sheet is provided, and the preparation method comprises: step S1, surface-treating the current collector to obtain the surface-treated current collector; step S2, immersing the surface-treated current collector in a silicon-containing active slurry to obtain the silicon-containing current collector; and step S3, coating a protective layer slurry on both side surfaces of the silicon-containing current collector to obtain the silicon-containing negative electrode sheet; wherein the porosity of the current collector is 85-95%, and the effective radius of the pores in the current collector is 0.15-0.5 mm.
[0012] Furthermore, in the above step S1, the surface treatment method is plasma modification treatment; and / or the atmosphere of the plasma modification treatment is N2 or O2, and / or the power of the plasma modification treatment is 500 to 1500 W, and / or the time of the plasma modification treatment is 30 to 60 s.
[0013] Furthermore, in the above step S1, the current collector is selected from any one or more of copper foam, modified copper foam, nickel foam and modified nickel foam.
[0014] Furthermore, in the above step S2, the silicon-containing active slurry includes a silicon-containing active material, a conductive agent and a first binder, and / or the solid content of the silicon-containing active slurry is 10-25%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 50-70%; and / or the conductive agent is selected from any one or more of conductive carbon black, carbon fiber, and carbon nanotubes, and / or the first binder is selected from any one or more of styrene-butadiene rubber, butadiene rubber, and modified styrene-butadiene rubber.
[0015] Furthermore, the protective layer slurry includes secondary graphite particles and a second binder, and / or the mass ratio of the secondary graphite particles to the second binder is 95:4 to 97:2; the secondary graphite particles are selected from any one or more of secondary carbonized artificial graphite particles, secondary uncoated artificial graphite particles and single graphite particles mixed with secondary graphite particles.
[0016] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned silicon-containing negative electrode sheet.
[0017] By applying the technical solution of the present invention, the present application can improve the capacity of the battery by doping the silicon-containing active material in the porous current collector. At the same time, the present application can effectively restrain the volume expansion of the silicon particles in the silicon-containing active material layer by using the three-dimensional porous current collector skeleton of the optimized porous current collector, thereby improving the cycle stability of the battery. Specifically, on the one hand, the porous current collector with the above porosity has a void, which can reduce the flow resistance loss of the silicon-containing active material during the flow process, thereby improving the permeability of the silicon-containing active material and firmly confining the silicon-containing active material in the pores of the porous current collector. On the other hand, the voids in the porous current collector with the above porosity help to further alleviate the volume expansion of the silicon-containing active material. Controlling the effective radius of the pores in the porous current collector within the above range can further reduce the flow resistance loss of the silicon-containing active material during the flow process, and the specific surface area of the porous current collector is reduced, and the influence of the adsorption force and the boundary layer on the flow of the silicon-containing active material is also reduced, thereby further increasing the permeability of the silicon-containing active material, and further improving the cycle performance of the battery. In addition, a protective layer is stacked on the surface of the porous current collector. The expansion of the protective layer itself is much lower than the volume expansion of the silicon particles, thereby further forming a better buffering effect on the volume expansion of the silicon particles, thereby enabling the silicon-containing negative electrode plate to maintain structural stability during the cycle process, and further being able to continuously prevent the silicon-containing active material in the porous current collector from being exposed to a large amount of electrolyte to produce side reactions, thereby further improving the cycle performance of the battery.
[0018] Specific implementation methods
[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0020] As analyzed in the background technology of this application, there is a problem in the prior art that the negative electrode current collector cannot effectively suppress the volume expansion of the silicon-based negative electrode active material, resulting in poor cycle performance of the battery. In order to solve the above problem, this application provides a silicon-containing negative electrode plate and a preparation method thereof, and a lithium-ion battery.
[0021] In a typical embodiment of the present application, a silicon-containing negative electrode plate is provided, which includes a porous current collector and a protective layer stacked on the surface of the porous current collector; wherein the pores of the porous current collector are filled with silicon-containing active materials, the porosity of the porous current collector is 20-50%, and the effective radius of the pores in the porous current collector is 0.05-0.2 mm.
[0022] The present application can improve the capacity of the battery by doping silicon-containing active materials in the porous current collector. At the same time, the present application can effectively restrain the volume expansion of silicon particles in the silicon-containing active material layer by using the three-dimensional porous current collector skeleton of the optimized porous current collector, thereby improving the cycle stability of the battery. Specifically, on the one hand, the porous current collector with the above porosity has a void, which can reduce the flow resistance loss of the silicon-containing active material during the flow process, thereby improving the permeability of the silicon-containing active material and firmly confining the silicon-containing active material in the pores of the porous current collector. On the other hand, the voids in the porous current collector with the above porosity help to further alleviate the volume expansion of the silicon-containing active material. Controlling the effective radius of the pores in the porous current collector within the above range can further reduce the flow resistance loss of the silicon-containing active material during the flow process, and the specific surface area of the porous current collector is reduced, and the influence of the adsorption force and the boundary layer on the flow of the silicon-containing active material is also reduced, thereby further increasing the permeability of the silicon-containing active material, and further improving the cycle performance of the battery. In addition, a protective layer is stacked on the surface of the porous current collector, and the expansion of the protective layer itself is much lower than the volume expansion of the silicon particles, thereby further forming a good buffering effect on the volume expansion of the silicon particles, thereby maintaining the structural stability of the silicon-containing negative electrode during the cycle, and further being able to continuously prevent the silicon-containing active material in the porous current collector from being exposed to a large amount of electrolyte to cause side reactions, thereby further improving the cycle performance of the battery. Among them, the effective radius of the pore is the average size of the pores in the porous current collector, which can characterize the fluid transmission characteristics of the entire porous structure.
[0023] In addition, it should be noted that before filling with silicon-containing active materials, the porosity of the above porous current collector of the present application is 85-95%, and the effective radius of the pores is 0.15-0.5 mm.
[0024] In one embodiment of the present application, the mass content of the silicon-containing active material in the porous current collector is 37-55%.
[0025] It is preferred to control the mass content of the silicon-containing active material in the porous current collector within the above range, which not only helps to increase the capacity of the battery, but also alleviates the problem of separation of the silicon-containing active material and the porous current collector caused by silicon volume expansion, thereby helping to improve the cycle performance of the lithium-ion battery.
[0026] In one embodiment of the present application, the surface density of the protective layer accounts for 20-50% of the total surface density of the silicon-containing negative electrode plate; and / or the surface density ratio of the protective layer and the porous current collector is 1:4-1:1.
[0027] It is preferred to control the ratio of the surface density of the protective layer to the total surface density of the silicon-containing negative electrode sheet and the surface density ratio of the protective layer to the porous current collector within the above range. The protective layer below the surface density range is too thin, which is not conducive to suppressing the large-scale contact between silicon and the electrolyte. The protective layer above the surface density range is too high, which is not conducive to improving the energy density of the silicon-containing negative electrode sheet. Therefore, the protective layer controlled within the above surface density range helps to alleviate the side reactions between the silicon-containing active material and the electrolyte in the porous current collector (high cycle performance) while taking into account the high energy density of the battery.
[0028] In one embodiment of the present application, any one or more of the secondary particle carbonized artificial graphite layer, the secondary particle uncoated artificial graphite layer and the single particle graphite mixed secondary particle graphite layer, and / or the protective layer has an OI value of 2.5 to 3.8.
[0029] The type of the protective layer is preferably within the above range, which helps to better inhibit the large-scale contact reaction between the silicon-containing active material and the electrolyte, thereby improving the cycle performance of the battery. The protective layer with an OI value within the above range is preferably not only highly isotropic, so that it not only has small cycle expansion, which is beneficial to improve the stability of the overall electrode structure, but also has a high rate performance, which is beneficial to the migration of lithium ions to the internal silicon active layer, wherein the OI value is a parameter of the order of the arrangement of graphite sheets in the graphite material, which is determined by X-ray diffraction.
[0030] In another typical embodiment of the present application, a method for preparing the above-mentioned silicon-containing negative electrode sheet is provided, and the preparation method comprises: step S1, surface-treating the current collector to obtain the surface-treated current collector; step S2, immersing the surface-treated current collector in a silicon-containing active slurry to obtain the silicon-containing current collector; and step S3, coating a protective layer slurry on both side surfaces of the silicon-containing current collector to obtain the silicon-containing negative electrode sheet; wherein the porosity of the current collector is 85-95%, and the effective radius of the pores in the current collector is 0.15-0.5 mm.
[0031] By performing surface treatment on the current collector in step S1, the hydrophilicity of the current collector can be improved, which is conducive to the penetration of the silicon-containing active slurry. After the surface treatment, the current collector is immersed in the silicon-containing active slurry in step S2, and the porosity of the current collector and the effective radius of the pores in the current collector are controlled within the above range, which can reduce the flow resistance loss of the silicon-containing active material in the infiltration of the current collector pores, so that the silicon-containing active slurry can fully penetrate into the pores of the current collector, thereby increasing the capacity of the battery. By coating the protective layer slurry on the two side surfaces of the silicon-containing current collector in step S3, the expansion of silicon particles can be buffered, so that the silicon-containing negative electrode plate can maintain structural stability during the cycle, thereby continuously preventing the silicon-containing active material in the current collector from being exposed to a large amount of electrolyte to produce side reactions, and further improving the cycle performance of the battery.
[0032] In one embodiment of the present application, in the above-mentioned step S1, the surface treatment method is plasma modification treatment; and / or, the atmosphere of the plasma modification treatment is N2 or O2, and / or, the power of the plasma modification treatment is 500~1500W, and / or, the time of the plasma modification treatment is 30~60s.
[0033] Surface treatment by plasma modification treatment and controlling the atmosphere, power and time of the plasma modification treatment within the above ranges can help improve the hydrophilicity of the current collector, thereby further improving the permeability of the silicon-containing active slurry in the current collector after surface treatment.
[0034] In one embodiment of the present application, in the above step S1, the current collector is selected from any one or more of foamed copper, modified foamed copper, foamed nickel and modified foamed nickel.
[0035] The above-mentioned types of current collectors not only have rich porous structures, but also have high compatibility between the current collector and the silicon-containing active slurry, which helps to improve the cycle stability of the silicon-containing negative electrode sheet.
[0036] In one embodiment of the present application, in the above step S2, the silicon-containing active slurry includes a silicon-containing active material, a conductive agent and a first binder, and / or the solid content of the silicon-containing active slurry is 10-25%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 50-70%; and / or the conductive agent is selected from any one or more of conductive carbon black, carbon fiber, and carbon nanotubes, and / or the first binder is selected from any one or more of styrene-butadiene rubber, butadiene rubber, and modified styrene-butadiene rubber.
[0037] The composition of the silicon-containing active slurry is preferably within the above range, and the types of the conductive agent and the first binder are preferably within the above range, which helps to improve the conductivity and permeability of the silicon-containing active slurry. It is preferred to control the mass content of the silicon-containing active material in the silicon-containing active slurry within the above range, which helps to improve the energy density of the battery. If the solid content of the silicon-containing active slurry is too low, it is not conducive to improving the loading efficiency of the active material; if the solid content of the silicon-containing active slurry is too high, it will increase the resistance to penetration to a certain extent, thereby affecting the penetration of the silicon-containing active slurry in the current collector after surface treatment. It is preferred to control the solid content of the silicon-containing active slurry within the above range to help improve the penetration efficiency and effect of the silicon-containing active slurry in the current collector after surface treatment. Therefore, controlling the solid content of the silicon-containing active slurry and the mass content of the silicon-containing active material within the above range helps to take into account the penetration effect of the silicon-containing active slurry and the current collector and the loading amount of the silicon-containing active slurry.
[0038] In one embodiment of the present application, the protective layer slurry includes secondary graphite particles and a second binder, and / or the mass ratio of the secondary graphite particles to the second binder is 95:4 to 97:2; the secondary graphite particles are selected from any one or more of secondary carbonized artificial graphite particles, secondary uncoated artificial graphite particles and single graphite particle mixed with secondary graphite particles.
[0039] The protective layer slurry includes secondary artificial graphite particles and a second binder to form a secondary artificial graphite particle layer, and the mass ratio of the secondary artificial graphite particles and the second binder and the type of the second binder are controlled within the above range, which helps to better inhibit the large-scale contact reaction between the silicon-containing active material and the electrolyte, thereby improving the cycle performance of the battery. Among them, the secondary artificial graphite particles selected in the secondary artificial graphite particle layer not only have high isotropy and small cycle expansion, which is conducive to improving the stability of the overall electrode structure, but also have high rate performance of the secondary artificial graphite particles, which is conducive to the migration of lithium ions to the internal silicon active layer.
[0040] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned silicon-containing negative electrode sheet.
[0041] The lithium-ion battery using the above-mentioned silicon-containing negative electrode plate as the negative electrode plate has excellent properties such as high energy density and cycle stability.
[0042] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0043] Example 1
[0044] The surface of the foam copper current collector was subjected to plasma modification treatment in a N2 atmosphere to obtain a surface-treated current collector, wherein the power of the plasma modification treatment was 1000 W and the time of the plasma modification treatment was 40 s.
[0045] The silicon-containing active slurry includes a silicon-containing active material, conductive carbon black and styrene-butadiene rubber, wherein the solid content of the silicon-containing active slurry is 15%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 60%. The surface-treated current collector is immersed in the silicon-containing active slurry to obtain a silicon-containing current collector, wherein the mass content of the silicon-containing active material in the silicon-containing current collector (porous current collector) is 55%.
[0046] The protective layer slurry includes 95% by mass of secondary particle carbonized artificial graphite and 4% of styrene-butadiene rubber. The protective layer slurry is coated on the surfaces of both sides of the silicon-containing current collector and then dried to form a secondary particle carbonized artificial graphite layer, thereby obtaining a silicon-containing negative electrode sheet including a porous current collector and a protective layer stacked on the surface of the porous current collector, wherein the OI value of the secondary particle carbonized artificial graphite layer is 3.4, the surface density of the secondary particle carbonized artificial graphite layer accounts for 30% of the total surface density of the silicon-containing negative electrode sheet, and the surface density ratio of the secondary particle carbonized artificial graphite layer to the porous current collector is 0.43:1.
[0047] Example 2
[0048] The surface of the foam copper current collector was subjected to plasma modification treatment in a N2 atmosphere to obtain a surface-treated current collector, wherein the power of the plasma modification treatment was 1000 W and the time of the plasma modification treatment was 40 s.
[0049] The silicon-containing active slurry includes a silicon-containing active material, conductive carbon black and styrene-butadiene rubber, wherein the solid content of the silicon-containing active slurry is 15%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 60%. The surface-treated current collector is immersed in the silicon-containing active slurry to obtain a silicon-containing current collector, wherein the mass content of the silicon-containing active material in the silicon-containing current collector (porous current collector) is 50%.
[0050] The protective layer slurry includes 97% by mass of secondary particle carbonized artificial graphite and 2% of styrene-butadiene rubber. The protective layer slurry is coated on the surfaces of both sides of the silicon-containing current collector and then dried to form a secondary particle carbonized artificial graphite layer, thereby obtaining a silicon-containing negative electrode sheet including a porous current collector and a protective layer stacked on the surface of the porous current collector, wherein the OI value of the secondary particle carbonized artificial graphite layer is 3.4, the surface density of the secondary particle carbonized artificial graphite layer accounts for 30% of the total surface density of the silicon-containing negative electrode sheet, and the surface density ratio of the secondary particle carbonized artificial graphite layer to the porous current collector is 0.43:1.
[0051] Example 3
[0052] The surface of the foam copper current collector was subjected to plasma modification treatment in a N2 atmosphere to obtain a surface-treated current collector, wherein the power of the plasma modification treatment was 1000 W and the time of the plasma modification treatment was 40 s.
[0053] The silicon-containing active slurry includes a silicon-containing active material, secondary particles of uncoated artificial graphite and styrene-butadiene rubber, wherein the solid content of the silicon-containing active slurry is 15%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 60%. The surface-treated current collector is immersed in the silicon-containing active slurry to obtain a silicon-containing current collector, wherein the mass content of the silicon-containing active material in the silicon-containing current collector (porous current collector) is 55%.
[0054] The protective layer slurry includes 70% by mass of uncoated secondary particle artificial graphite and 30% by mass of styrene-butadiene rubber. The protective layer slurry is coated on the surfaces of both sides of the silicon-containing current collector and then dried to form a layer of uncoated secondary particle artificial graphite, thereby obtaining a silicon-containing negative electrode sheet including a porous current collector and a protective layer stacked on the surface of the porous current collector. The surface density of the uncoated secondary particle artificial graphite layer accounts for 30% of the total surface density of the silicon-containing negative electrode sheet, and the surface density ratio of the carbonized secondary particle artificial graphite layer to the porous current collector is 0.43:1.
[0055] The porosity and effective radius of the pores of the foam copper current collector in Examples 4 to 7 were changed (see Table 1 for details).
[0056] Example 8
[0057] The difference from Example 1 is that the mass content of the silicon-containing active material in the porous current collector is 45%, and a silicon-containing negative electrode plate is finally obtained.
[0058] Example 9
[0059] The difference from Example 1 is that the mass content of the silicon-containing active material in the porous current collector is 37%, and a silicon-containing negative electrode plate is finally obtained.
[0060] Example 10
[0061] The difference from Example 1 is that the mass content of the silicon-containing active material in the porous current collector is 60%, and a silicon-containing negative electrode plate is finally obtained.
[0062] Embodiment 11
[0063] The difference from Example 1 is that the surface density of the secondary particle artificial carbonized graphite layer accounts for 20% of the total surface density of the silicon-containing negative electrode plate, and the surface density ratio of the secondary particle artificial carbonized graphite layer and the porous current collector is 1:4, and finally a silicon-containing negative electrode plate is obtained.
[0064] Example 12
[0065] The difference from Example 1 is that the surface density of the secondary particle artificial carbonized graphite layer accounts for 50% of the total surface density of the silicon-containing negative electrode plate, and the surface density ratio of the secondary particle artificial carbonized graphite layer and the porous current collector is 1:1, and finally a silicon-containing negative electrode plate is obtained.
[0066] Embodiment 13
[0067] The difference from Example 1 is that the surface density of the secondary particle artificial carbonized graphite layer accounts for 10% of the total surface density of the silicon-containing negative electrode plate, and the surface density ratio of the secondary particle artificial graphite layer and the porous current collector is 1:9, and finally a silicon-containing negative electrode plate is obtained.
[0068] Embodiment 14
[0069] The difference from Example 1 is that the OI value of the secondary particle artificial carbonized graphite layer is 3.8, and a silicon-containing negative electrode plate is finally obtained.
[0070] Embodiment 15
[0071] The difference from Example 1 is that the OI value of the secondary particle carbonized artificial graphite layer is 5.3, and a silicon-containing negative electrode plate is finally obtained.
[0072] Example 16
[0073] The difference from Example 1 is that the power of the plasma modification treatment is 500 W, the time of the plasma modification treatment is 30 s, and finally a silicon-containing negative electrode plate is obtained.
[0074] Embodiment 17
[0075] The difference from Example 1 is that the power of the plasma modification treatment is 100 W, the time of the plasma modification treatment is 3 s, and finally a silicon-containing negative electrode plate is obtained.
[0076] Embodiment 18
[0077] The difference from Example 1 is that the solid content of the silicon-containing active slurry is 10%, the mass content of the silicon-containing active material in the silicon-containing active slurry is 70%, and finally a silicon-containing negative electrode sheet is obtained.
[0078] Embodiment 19
[0079] The difference from Example 1 is that the solid content of the silicon-containing active slurry is 10%, the mass content of the silicon-containing active material in the silicon-containing active slurry is 90%, and finally a silicon-containing negative electrode sheet is obtained.
[0080] Comparative Example 1
[0081] The difference from Example 2 is that the copper foil current collector is directly coated with silicon active slurry to serve as the silicon-containing negative electrode plate.
[0082] Comparative Example 2
[0083] The difference from Example 2 is that the porosity of the foam copper current collector is 70%, wherein the effective radius of the pores is 0.05 mm, and finally a silicon-containing negative electrode plate is obtained.
[0084] Comparative Example 3
[0085] The difference from Example 2 is that the foam copper current collector is directly immersed in the silicon-containing active slurry to obtain the silicon-containing current collector, and finally obtain the silicon-containing negative electrode plate.
[0086] Test Method
[0087] Porosity test: The test is carried out according to GB / T 21650.1-2008 "Mercury Intrusion Porosimetry and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials Part 1: Mercury Intrusion Porosimetry".
[0088] Effective pore radius test: Tested according to GB / T 21650.1-2008 "Mercury Intrusion Porosimetry and Gas Adsorption Method for Determination of Pore Size Distribution and Porosity of Solid Materials Part 1: Mercury Intrusion Porosimetry", measured by scanning microscope.
[0089] Surface density test: weigh and measure the protective layer, porous current collector and silicon-containing negative electrode plate. Surface density = mass / area.
[0090] Capacity retention test: electrochemical cycle test.
[0091] The silicon-containing negative electrode sheets and positive electrode sheets, separators and electrolytes of the above embodiments and comparative examples were assembled into lithium-ion batteries for performance testing. The test results are shown in Table 1.
[0092] Lithium battery preparation: NCM positive electrode sheet, the above silicon-containing negative electrode sheet and diaphragm are laminated to form a lithium-ion battery with a thickness of 0.5mm, a width of 6cm and a length of 8cm, and a capacity of 0.05Ah. They are vacuum-baked at 80°C for 12 hours, injected with electrolyte, and assembled into a single-layer laminated soft-pack lithium-ion battery through packaging, shelving, and dissolving and capacitating. Dissolved and capacitated, the battery is tested for 1C / 1C cycle offline.
[0093] Table 1
[0094]
[0095] It should be noted that the current collectors in Table 1 are not filled with silicon-containing active materials, and the copper foil current collector in Comparative Example 1 has no pores.
[0096] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0097] The present application can improve the capacity of the battery by doping silicon-containing active materials in the porous current collector. At the same time, the present application can effectively restrain the volume expansion of silicon particles in the silicon-containing active material layer by using the three-dimensional porous current collector skeleton of the optimized porous current collector, thereby improving the cycle stability of the battery. Specifically, on the one hand, the porous current collector with the above porosity has a void, which can reduce the flow resistance loss of the silicon-containing active material during the flow process, thereby improving the permeability of the silicon-containing active material and firmly confining the silicon-containing active material in the pores of the porous current collector. On the other hand, the voids in the porous current collector with the above porosity help to further alleviate the volume expansion of the silicon-containing active material. Controlling the effective radius of the pores in the porous current collector within the above range can further reduce the flow resistance loss of the silicon-containing active material during the flow process, and the specific surface area of the porous current collector is reduced, and the influence of the adsorption force and the boundary layer on the flow of the silicon-containing active material is also reduced, thereby further increasing the permeability of the silicon-containing active material, and further improving the cycle performance of the battery. In addition, a protective layer is stacked on the surface of the porous current collector. The expansion of the protective layer itself is much lower than the volume expansion of the silicon particles, thereby further forming a better buffering effect on the volume expansion of the silicon particles, thereby enabling the silicon-containing negative electrode plate to maintain structural stability during the cycle process, and further being able to continuously prevent the silicon-containing active material in the porous current collector from being exposed to a large amount of electrolyte to produce side reactions, thereby further improving the cycle performance of the battery.
[0098] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A silicon-containing negative electrode plate, characterized in that: The silicon-containing negative electrode plate comprises a porous current collector and a protective layer stacked on the surface of the porous current collector; The pores of the porous current collector are filled with silicon-containing active materials, the porosity of the porous current collector is 20-50%, and the effective radius of the pores in the porous current collector is 0.05-0.2 mm.
2. The silicon-containing negative electrode sheet according to claim 1, characterized in that: The mass content of the silicon-containing active material in the porous current collector is 37-55%.
3. The silicon-containing negative electrode sheet according to claim 1 or 2, characterized in that: The surface density of the protective layer accounts for 20-50% of the total surface density of the silicon-containing negative electrode plate; and / or the ratio of the surface density of the protective layer to that of the porous current collector is 1:4-1:
1.
4. The silicon-containing negative electrode sheet according to any one of claims 1 to 3, characterized in that: The protective layer is selected from any one or more of a secondary particle carbonized artificial graphite layer, a secondary particle uncoated artificial graphite layer and a single particle graphite mixed with a secondary particle graphite layer, and / or the OI value of the protective layer is 2.5-3.
8.
5. A method for preparing the silicon-containing negative electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, performing surface treatment on the current collector to obtain a surface-treated current collector; Step S2, immersing the surface-treated current collector in a silicon-containing active slurry to obtain a silicon-containing current collector; and Step S3, coating a protective layer slurry on both side surfaces of the silicon-containing current collector to obtain the silicon-containing negative electrode plate; The porosity of the current collector is 85-95%, and the effective radius of the pores in the current collector is 0.15-0.5 mm.
6. The preparation method according to claim 5, characterized in that: In step S1, the surface treatment method is plasma modification treatment; and / or the atmosphere of the plasma modification treatment is N2 or O2, and / or the power of the plasma modification treatment is 500 to 1500 W, and / or the time of the plasma modification treatment is 30 to 60 s.
7. The preparation method according to claim 5 or 6, characterized in that: In the step S1, the current collector is selected from any one or more of foamed copper, modified foamed copper, foamed nickel and modified foamed nickel.
8. The preparation method according to any one of claims 5 to 7, characterized in that: In step S2, the silicon-containing active slurry includes a silicon-containing active material, a conductive agent and a first binder, and / or the solid content of the silicon-containing active slurry is 10-25%, and the mass content of the silicon-containing active material in the silicon-containing active slurry is 50-70%; And / or, the conductive agent is selected from any one or more of conductive carbon black, carbon fiber, and carbon nanotubes, and / or, the first binder is selected from any one or more of styrene-butadiene rubber, butadiene rubber, and modified styrene-butadiene rubber.
9. The preparation method according to any one of claims 5 to 8, characterized in that: The protective layer slurry includes secondary graphite particles and a second binder, and / or the mass ratio of the secondary graphite particles to the second binder is 95:4 to 97:2; the secondary graphite particles are selected from any one or more of secondary carbonized artificial graphite particles, secondary uncoated artificial graphite particles and single-particle graphite mixed with secondary graphite particles.
10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode plate is the silicon-containing negative electrode plate according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of negative pole piece and secondary battery
CN117410435A
All-solid-state battery silicon-based negative electrode, preparation method thereof and all-solid-state battery
CN117577854A
Cited By
Preparation method of silicon wafer negative electrode for solid-state battery
CN121076077A
Negative plate, preparation method of negative plate and battery
CN121862686A